Immune Dysregulation in SARS-CoV-2 patients coinfected with Mycobacterium tuberculosis (Mtb) or HIV in China - Lei Li; Jianxiang Zhang; Ranran Sun; Hong Liu; Genyang Cheng; Feifei Fan; Chong Wang; Ang Li; Hongxia Liang; Zujiang Yu; Guiqiang Wang; Zhigang Ren (BMC, 2024)
Abstract Background SARS-CoV-2 infections usually cause immune dysregulation in the human body. Studies of immunological changes resulting from coinfections with Mycobacterium tuberculosis (Mtb) or HIV are limited. Methods We conducted a retrospective study focusing on patients with COVID-19. A total of 550 patients infected with SARS-CoV-2 were enrolled in our study and categorized into four groups based on the presence of coinfections; 166 Delta-infected patients, among whom 103 patients had no coinfections, 52 who were coinfected with Mtb, 11 who were coinfected with HIV, and 384 Omicron-infected patients. By collecting data on epidemiologic information, laboratory findings, treatments, and clinical outcomes, we analyzed and compared clinical and immunological characteristics. Results Compared with those in the Delta group, the median white blood cell, CD4 + T-cell and B-cell counts were lower in the Mtb group and the HIV group. Except for those in the Omicron group, more than half of the patients in the three groups had abnormal chest CT findings. Among the three groups, there were no significant differences in any of the cytokines. Compared with those in the Delta group, the disease duration and LOS were longer in the Mtb group and the HIV group. For unvaccinated Delta-infected patients, in the Mtb and HIV groups, the number of B cells and CD4 + T cells was lower than that in the Delta group, with no significant difference in the LOS or disease duration. In the Mtb group, three (6%) patients presented with a disease duration greater than four months and had decreased lymphocyte and IL17A counts, possibly due to double infections in the lungs caused by SARS-CoV-2 and M. tuberculosis. Conclusions We found that SARS-CoV-2 patients coinfected with Mtb or HIV exhibited a longer disease duration and longer LOS, with a decrease in B cells and CD4 + T cells, suggesting that these cells are related to immune function. Changes in cytokine levels suggest that coinfection with Mtb or HIV does not result in dysregulation of the immune response. Importantly, we discovered a chronic course of coinfection involving more than four months of Mtb and SARS-CoV-2 infection.